2013
DOI: 10.3174/ajnr.a3640
|View full text |Cite
|
Sign up to set email alerts
|

3T MRI Quantification of Hippocampal Volume and Signal in Mesial Temporal Lobe Epilepsy Improves Detection of Hippocampal Sclerosis

Abstract: BACKGROUND AND PURPOSE:In mesial temporal lobe epilepsy, MR imaging quantification of hippocampal volume and T2 signal can improve the sensitivity for detecting hippocampal sclerosis. However, the current contributions of these analyses for the diagnosis of hippocampal sclerosis in 3T MRI are not clear. Our aim was to compare visual analysis, volumetry, and signal quantification of the hippocampus for detecting hippocampal sclerosis in 3T MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(139 citation statements)
references
References 33 publications
4
123
0
4
Order By: Relevance
“…Furthermore, as we only utilized T1 MRI data and did not incorporate signal variation from T2/FLAIR scans (Coan et al, 2014, Cantor-Rivera et al, 2015 or alterations found in PET (Kerr et al, 2013) or DTI data (Cantor-Rivera et al, 2015), it is clear that there is still much room for improving classifier performance. Thus, in the future, an even more comprehensive model that identifies subgroups, incorporates other imaging modalities in addition to clinical and neuropsychological data, would likely be superior in regards to both diagnosis and predicting treatment outcomes, thus achieving clinical utility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as we only utilized T1 MRI data and did not incorporate signal variation from T2/FLAIR scans (Coan et al, 2014, Cantor-Rivera et al, 2015 or alterations found in PET (Kerr et al, 2013) or DTI data (Cantor-Rivera et al, 2015), it is clear that there is still much room for improving classifier performance. Thus, in the future, an even more comprehensive model that identifies subgroups, incorporates other imaging modalities in addition to clinical and neuropsychological data, would likely be superior in regards to both diagnosis and predicting treatment outcomes, thus achieving clinical utility.…”
Section: Discussionmentioning
confidence: 99%
“…Using a linear discriminant analysis McDonald et al (2008) showed that lateral temporal cortical thickness could significantly discriminate TLE patients from controls with 74% accuracy. By focusing solely on quantification of hippocampal volume and T2 signal changes, computer-aided methods were shown to improve detection of MTS by 28% compared to visual analysis alone (Coan et al, 2014). Using a voxel-based approach for white and gray matter segmentation as well as voxel based DTI measures, Focke et al (2012) were able to distinguish TLE with MTS from controls with greater than 88% accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study that tested the ability of conventional manual segmentation and two automatic segmentation methods for measuring hippocampal volume found that the manual method was more sensitive than both automated methods, and suggested that manual segmentation should still be used as the standard technique for volume measurements. [42] Furthermore, most of the automatic techniques are not completely automated and require manual intervention to outline the callosal boundaries. [43] The disadvantages of the manual method are: (i) results can be influenced by factors such as anatomical protocols, tracer experience, scan acquisition parameters and image quality; (ii) some authors consider that manual tracings are time consuming, but we think that this depends on the examined structure's complexity, and the CC is not a complex structure for tracing.…”
Section: Discussionmentioning
confidence: 99%
“…(d) [20,21] In these cases, advanced techniques of imaging including magnetic resonance spectroscopy (MRS), interictal FDG-PET, ictal SPECT (Figure 9), quantitative analysis of hippocampus formation such as volumetry and relaxometry, [22][23][24][25] can be useful tools for diagnostic and lateralization of seizure onset ( Figure 6). …”
Section: Mtle With Normal Mrimentioning
confidence: 99%